PERSPEKTIF ETIS ARTIFICIAL INTELLIGENCE DALAM AKUNTANSI MANAJEMEN - Endang Tri Pratiwi; Hamid Habbe, Abdul; Syarifuddin, Syarifuddin; Rura, Yohanis; Irdam Ferdiansah, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Artificial Intelligence (AI) and Robotic Process Automation (RPA) play a central role in the transformation of accounting and auditing practices. RPA focused on process automation, simplifies regulatory tasks such as data entry, while AI relying on quality of data, involves technologies such as data mining, machine learning, and natural language processing. This paper aims to explore the literature that investigates the ethical impact of artificial intelligence (AI) on management accounting during the adoption process. This paper uses conceptual analysis through a scientific literature approach from reputable journal databases in the fields of accounting, technology and information systems. Data collection was carried out in the period March to May 2024. Based on our literature review, we found that data security, privacy and misuse, accountability, Accessibility, benefits and challenges, and AI transparency and trustworthiness are among the most common ethical risks in the development and use of AI in management accounting. Ethical issues arising from the use of AI in management accounting have three characteristics.